Steller's eider (Polysticta stelleri) in northern Europe and northwest Russia (data from Petersen et al. 2006)-reference-data - Petersen, Margaret R.; Douglas, David (Movebank Data Repository, 2015)
Petersen MR, Bustnes JO, Systad GH (2006) Breeding and moulting locations and migration patterns of the Atlantic population of Steller's eiders Polysticta stelleri as determined from satellite telemetry. Journal of Avian Biology 37(1), 58–68. doi:10.1111/j.0908-8857.2006.03472.x : This study was designed to determine the spring, summer, autumn, and early winter distribution, migration routes, and timing of migration of the Atlantic population of Steller's eiders Polysticta stelleri. Satellite transmitters were implanted in 20 eiders captured in April 2001 at Vadsø, Norway, and their locations were determined from 5 May 2001 to 6 February 2002. Regions where birds concentrated from spring until returning to wintering areas included coastal waters from western Finnmark, Norway, to the eastern Taymyr Peninsula, Russia. Novaya Zemlya, Russia, particularly the Mollera Bay region, was used extensively during spring staging, moult, and autumn staging; regions of the Kola, Kanin, and Gydanskiy peninsulas, Russia, were used extensively during spring and moult migrations. Steller's eiders migrated across the Barents and Kara seas and along the Kara Sea and Kola Peninsula coastal waters to nesting, moulting, and wintering areas. The majority of marked eiders (9 of 15) were flightless in near-shore waters along the west side of Novaya Zemlya. Eiders were also flightless in northern Norway and along the Kanin and at Kola Peninsula coasts. We compare and contrast natural history characteristics of the Atlantic and Pacific populations and discuss evolutionary and ecological factors influencing their distribution.